2020
DOI: 10.20944/preprints202005.0296.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

W-Band Millimeter Waves Targeted Mortality of H1299 Human Lung Cancer Cells without Affecting Non-tumorigenic MCF-10A Human Epithelial Cells In Vitro

Abstract: Therapeutically effective treatments of cancer are limited. To calibrate the efficiency of the novel technique we recently discovered to modulate cancer cell viability using tuned electromagnetic fields; H1299 human lung cancer cells were irradiated in a sweeping regime of W-band (75-105 GHz) millimeter waves (MMW) at 0.2 mW/cm2 (2 W/m2). Effects on cell morphology, cell death and senescence were examined and compared to that of non-tumorigenic MCF-10A human epithelial cells. MMW irradiation led to alterations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Thermal ablation techniques have been employed as the other alternative but with restricted application in order not to burn normal cells/tissues during treatment. Our experiments demonstrated that non-ionizing MMW (75-105 GHz) exposure with a non-thermal power density of 0.2 mW/cm 2 can elicit morphological changes in H1299 human lung cancer cells [4] leading to targeted apoptosis and mortality [5] without harming normal cells under the same exposure conditions. MMWs are also reported to be helpful for detecting different types of cancers [6].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Thermal ablation techniques have been employed as the other alternative but with restricted application in order not to burn normal cells/tissues during treatment. Our experiments demonstrated that non-ionizing MMW (75-105 GHz) exposure with a non-thermal power density of 0.2 mW/cm 2 can elicit morphological changes in H1299 human lung cancer cells [4] leading to targeted apoptosis and mortality [5] without harming normal cells under the same exposure conditions. MMWs are also reported to be helpful for detecting different types of cancers [6].…”
Section: Introductionmentioning
confidence: 79%
“…MMW treatment is known to result in membrane depolarizations resulting in the loss of integral charge status and direction [8] at specific threshold power densities dependent on the number of cells under target, which could trigger such translocation events of signaling proteins activating the corresponding cascade processes. Sweeping frequency regimes over 75 -105 GHz at 0.2 mW/cm 2 resulted in apoptosis of H1299 lung cancer cells [5] and is likely to have arisen from such electromagnetic modulation of charge separated membranes activating signaling cascade processes. Experimentally, irradiation at 35 GHz is reported to activate the apoptotic caspase pathway in A375 melanoma cells in vitro [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation